THE EFFECT OF PRINCIPAL'S LEADERSHIP AND EDUCATIONAL PERFORMANCE ON IMPROVING THE QUALITY OF EDUCATION IN MTS BUSTANUL'ULUM GUPPI TEBING TINGGI CITY - M. Alang Khairun Nizar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The research method used is a descriptive survey method that describes social phenomena by examining the influence of Principal Leadership and Educational Personnel Performance (X) on Education Quality Improvement (variable Y). This study uses quantitative analysis techniques through path analysis which is intended to determine the magnitude of the influence of the Principal Leadership and Education Personnel Performance variables on improving the quality of education at MTs Bustanul'Ulum GUPPI Tebing Tinggi City, either simultaneously or partially. The results showed that the Principal's Leadership and Educational Personnel Performance had an effect on the Quality Improvement of Graduates at MTs Bustanul'Ulum GUPPI Tebing Tinggi City. The Principal's Leadership Variables and the Performance of Education Personnel were tested in influencing the Quality Improvement of Graduates at MTs Bustanul'Ulum GUPPI Tebing Tinggi City: Based on the SPSS calculation, the Fcount value is 6,302. with a = 5%, dk in the numerator: k, dk in the denominator: n-k-1 (5%;2;41) the f table value is 3.23. From the description, it can be seen that F Count (6.302) > F Table (3.23), with a significance of 0.004 < 0.05, it can be concluded that the hypothesis is accepted. From the calculation results of the SPSS program, the t-count value is 0.592 with a = 5%, t table (5%; n-k = 42) the t-table value is 2.018. From the description, it can be seen that the value of tcount (0.592 ) < t table (2.018), as well as the significance value of 0.557 > 0.05, it can be concluded that the first hypothesis is rejected. This means that leadership does not affect the quality of education.From the calculation results of the SPSS program, the t-count value is 2.625 with a = 5%, t table (5%; n-k = 42) the t-table value is 2.018. From the description, it can be seen that the value of tcount (2.625) > t table (2.018), as well as the significance value of 0.012 <0.05, it can be concluded that the second hypothesis is accepted. This means that the performance of education personnel affects the quality of education.